Tygodnik „Wprost” jako forum dyskusji nad obliczem polskiej szkoły w latach 1998–2017 - Gołębiowski, Dariusz (Biuletyn Historii Wychowania, 2023)
Late 1989 did not bring about any structural changes in education. For the next decade, a two-tier system of general education was in place, based on an 8-year primary school and a 4-year secondary school. This system was established in Poland in 1961 and remained unchanged until the late 20th century (1999) when Professor Mirosław Handke adopted a fundamental reform of the educational system, including introduction of 6-year primary schools, 3-year lower secondary schools and 3-year specialised high schools. Discussions on the changes, the course of the reform and the needs of Polish schools in the new reality were reflected in opinion weeklies. The article offers a concise analysis of texts on the perception of the structural reform, but also the broadly defined economic condition of Polish schools, the social position of teachers and school problems of children and adolescents, printed in Wprost weekly in 1998–2017. The latter date refers to the first year of Anna Zalewska’s reform, abolishing lower secondary schools and restoring the previous model of education.